Psychometric Properties of the MBI-SS for South African university students - Jorina Smit; Karina Mostert; Charlize du Toit; Leon De Beer; Arnold B. Bakker (SA Journal of Industrial Psychology)
Orientation: Student burnout has become increasingly evident among university students. However, to measure student burnout accurately in the South African context, it is essential to use validated, fair and unbiased instruments.